Can the Ti(OiPr)4/nBuLi combination of reagents function as a catalyst for [2+2+2] alkyne cyclotrimerisation reactions?12. (23rd November 2018) - Siemiaszko, Gabriela; Six, Yvan
Abstract : Catalysis of the cyclotrimerisation of alkynes with the Ti(OiPr)4 / n BuLi system was studied, leading to the development of a particularly convenient and reliable protocol. Abstract : Catalysis of the cyclotrimerisation of alkynes with the Ti(OiPr)4 / n BuLi system was studied, leading to the development of a particularly convenient and reliable protocol. This method allows the [2+2+2] cycloaddition reaction to proceed within a few minutes under microwave conditions, with generally good selectivity from a variety of aromatic and aliphatic alkynes.